2021
DOI: 10.1152/ajpheart.00897.2020
|View full text |Cite
|
Sign up to set email alerts
|

Vascular alterations among young adults with SARS-CoV-2

Abstract: This study was the first to investigate the vascular implications of contracting SARS-CoV-2 among young, otherwise healthy adults. Using a cross-sectional design, this study assessed vascular function 3–4 wk after young adults tested positive for SARS-CoV-2. The main findings from this study were a strikingly lower vascular function and a higher arterial stiffness compared with healthy controls. Together, these results suggest rampant vascular effects seen weeks after contracting SARS-CoV-2 in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
201
4
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(228 citation statements)
references
References 31 publications
18
201
4
5
Order By: Relevance
“…In the current case study, multiple assessments of vascular endothelial function, including FMD, reactive hyperemia, and PLM-induced hyperemia were lower at V2 , when the young woman was predominantly presymptomatic. Recent work by Ratchford et al ( 38 ) reported similar and marked reductions in FMD and PLM in young healthy men and women 3–4 wk after mild-to-moderate infection. Together, these findings suggest that vascular dysfunction is likely an early pathophysiological response to COVID-19, evident across macrovascular and microvascular compartments, and a critical component of COVID-19 sequelae that persists for weeks after infection.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the current case study, multiple assessments of vascular endothelial function, including FMD, reactive hyperemia, and PLM-induced hyperemia were lower at V2 , when the young woman was predominantly presymptomatic. Recent work by Ratchford et al ( 38 ) reported similar and marked reductions in FMD and PLM in young healthy men and women 3–4 wk after mild-to-moderate infection. Together, these findings suggest that vascular dysfunction is likely an early pathophysiological response to COVID-19, evident across macrovascular and microvascular compartments, and a critical component of COVID-19 sequelae that persists for weeks after infection.…”
Section: Discussionmentioning
confidence: 78%
“…Circulating markers of endothelial function and endotheliopathy were not assessed in this case study, which limits direct comparison with recent studies reporting elevated markers of endothelial injury and endotheliopathy in patients with critical COVID-19 infection ( 69 , 70 ). Further investigation examining endothelial responses to COVID-19 are certainly warranted, as current data indicates that functional measures of vascular endothelial dysfunction (FMD, hyperemia, and PLM) are impaired in mild cases of COVID-19 ( 38 ), whereas elevated markers of endothelial injury and endotheliopathy may be reserved for critical cases of COVID-19 ( 69 , 70 ). Lastly, due to significant fatigue and intermittent bouts of vigorous coughing, the participant opted out of additional laboratory-based follow up, which precluded the collection of additional, potentially very insightful data regarding COVID-19 and PASC.…”
Section: Discussionmentioning
confidence: 99%
“…with healthy control subjects (Ratchford et al, 2020). Likewise, a recent study using the rudimentary measure of pulse pressure as an arterial stiffness index has revealed an association between pulse pressure and all-cause mortality in patients with SARS-CoV-2 (Rodilla et al, 2021).…”
Section: New Findingsmentioning
confidence: 96%
“…Based on data of a recent study on a similar patient population [41], a sample of 63 patients was considered necessary to detect an expected pre-defined increase in FMD from baseline values of ≥40% with a power of 80% and a level of significance of 5%. To account for possible drop-outs or technical failures during FMD measurements, we planned to screen ≈100 patients for eligibility.…”
Section: Sample Sizementioning
confidence: 99%